Ethicality, Quality, and Learners' Necessities: Educational Technology Participation - Sunmi, Sunmi; Manik, Willy Diva; Apsela, Eztevania Bhea; Munthe, Yesyurun; Adinata, Naftali (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2023)
Nowadays, the times are growing rapidly, demanding various fields to improve their quality, especially in the world of education. Sustainable education does not only focus on schools located in urban areas, but also voices coming from schools in certain areas, far from the boisterous development of technology, according to the authors have to be heard as a main voice in an investigation. In particular, significant voices emanate out of SMA Negeri 1 Kapuas Hilir and SMK Negeri 1 Kuala Kapuas, Central Kalimantan. Furthermore, it aimed to analyze the methods of improving educational performance in schools. The qualitative method used throughout the interview process involved collecting data from three interviewees or research subjects. Based on gathering data, information, and facts, the researchers found that: educational quality is determined by input factors (condition of students), process (creation of learning atmosphere), and environment (family, community, and nature), as well as facilities and infrastructure (devices that facilitate learning activities). Improving educational performance requires teachers' professionalism as it influences the advancement of educational development in SMA Negeri 1 Kapuas Hilir and SMK Negeri 1 Kuala Kapuas, Central Kalimantan. The results showed that there are directions and activities in upgrading, seminars, training, conducting inter-school visits to gain experience from other school teachers as a source of reference. Furthermore, based on reevaluation, teachers and education officials through research on other schools, saw unique and important steps forward when they looked at the lens of educational problems located in locations distant from hustle and technology acceleration.